Ludebant coram Deo. On Legitimacy of Dance in XVIth Century Corpus Christi (Castilla. Estudios de Literatura, 2015)
It is beyond doubt that dances form part of the complex field of XVIth Century  religious, secular and liturgical festivals. This paper considers dance as a manifestation of XVIth Century Corpus Christi and deals with a purely hermeneutical question: the way its role is ideologically legitimated into religious festivities, as well as some of its theatrical components. As a result of a process of integration of different codes in the complex of Early Renaissance theatre, we should think about dance from a typological point of view to understand its sense inside the performance
Keywords: dance; Corpus Christi; theatricality; XVIth century; Bible